A New Tool to Acquire Sheet Metal Cyclic Plasticity Data for Hardening Models - Jasri, Mohamad (GSTF, 2016)
Predictive methods using finite element appear to be the most effective way to identify and solve defects such as springback in sheet metal forming. The accuracy of the predictions depends upon the application of accurate plasticity modelling. A model that is capable to consider the Baushinger effect and cyclic hardening characteristic. This model can be represented by several constitutive equations such as kinematic hardening model, isotropic hardening model or mixed hardening model. Experimental devices and methods are being continuously improved to incorporate increasingly accurate plastic bending characteristics. Part of the task is to improve the methods in acquiring material behaviour. For that a new tool has been developed to test and record the characteristics of sheet metal deformation by investigating the Bauschinger effect factors (BEF) and cyclic hardening behaviour. The developed tool is believed to simulate the actual forming conditions of bending and unbending loading. An initial experimental investigation shows that the tool is capable to record sheet metal behaviour under cyclic loading. The results are analysed for sign of Bauschinger effect and cyclic hardening. It was found that the Bauschinger effect does occur during bending and unbending loadings in sheet metal forming. The BEF value was found to increase as the thickness increases. It was also found that the existence of work hardening stagnation in the cyclic stress-strain curves is not observed. This acquired material characteristic is significant for providing more reliable data in identifying material parameters of the related hardening models. Thus improve the material models as well as the finite element simulation of sheet metal forming